Cardiac effusion and serum biochemical abnormalities of Salmonella gallinarum infection in point of lay pullets - Okafor, SC; Ihedioha, JI; Ezema, WS (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to evaluate some lesions and biochemical abnormalities of fowl typhoid (FT) in point of lay (POL) pullets. Fifty POL pullets were randomly assigned to two groups of 25 infected orally with S. gallinarum (109 S. gallinarum colony forming units (CFUs)/mL), and 25 uninfected controls. Blood samples were collected from four randomly selected pullets in each group weekly for 35 days post infection (PI), and the harvested serum used for biochemical evaluations, following standard techniques. Relevant tissues were processed for histopathology. Significant (P < 0.05) loss of body weight, 48% morbidity, 12% overall mortality, significant drop in egg production and severe pericardial effusion were observed in the infected pullets when compared to the uninfected controls. There was significantly (P < 0.05) higher serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), superoxide dismutase (SOD) and catalase (CAT) activities, malondialdehyde (MDA), serum total protein, globulin, total cholesterol, total bilirubin, uric acid, and creatinine levels, and lower serum albumin level in the infected POL pullets than that of the uninfected controls on days 7, 14, 21, 28 and 35 PI. The assayed biochemical parameters variably correlated with egg production, with MDA, SOD and CAT highly significant (P < 0.01). Inflammatory, degenerative and necrotic changes were observed in the heart, liver, spleen, kidneys, lungs, intestine and ovary of the infected POL pullets. Based on the significant elevation in MDA level in the infected POL pullets when compared to the uninfected controls coupled with highly significant correlation between the MDA, and egg production, oxidative stress (OS) may play a significant role in the pathology caused by FT. An association was established between elevated OS markers with antioxidant properties (SOD and CAT) and clinical outcome, including survival/health improvement indices such as improved weight gain and egg production as well as low mortality rate in an acute disease like FT. This suggests that inclusion of antioxidants in the treatment of FT in POL pullets may further ameliorate morbidity, development of lesions, improve weight gain and egg production, and reduce mortality, more so, considering the global menace of antimicrobial resistance.